Meningkatkan Hasil Belajar Geografi Siswa dengan Menggunakan Model Pembelajaran Problem Based Learning Kelas XI IPS 1 SMA Negeri 4 Bombana Pada Materi Mitigasi Bencana Alam - Sarmita; Andrias; La Ode Nursalam; La Ode Amaluddin (Jurnal Penelitian Pendidikan Geografi, 2024)
One of the problems at Senior High School 4 Bombana is that student learning outcomes do not reach the minimum completeness criteria. The use of conventional methods and media makes students passive, besides that learning is only teacher-centered. The aims of this research are: 1) to describe an overview of students' Geography learning activities; 2) to describe the description of the teacher's teaching activities; and 3) to describe an overview of the improvement in learning outcomes of class XI IPS 1 students at Senior High School 4 Bombana who were taught using the Problem-Based Learning model on Natural Disaster Mitigation material. This type of research is Classroom Action Research with research subjects consisting of teachers and students of class XI IPS 1. Based on data analysis, the conclusions obtained are: 1) student learning activity in cycle I was 2.4 and cycle II increased to 3.6;2) teacher teaching activity in cycle I was 2.9, increasing to 3.7; and 3) student learning outcomes in cycle I were 65% (17/26 students completed) in cycle II increased to 92% (24/26 students completed).